INFORMASI PRODUK DALAM IKLAN DAN PERLINDUNGAN KONSUMEN INDONESIA - Fransisca Mulyono (Bina Ekonomi, 2010)
Commercial is still perceived as an interesting tools for producers and marketers because of its reliability to market their products, especially children's product. One of the main benefits of commercial is its ability in giving information to consumers about certain products. Although in Indonesia we have Undang-undang Perlindungan Konsumen, declared in 1999, lndonesia's consumer still have a wea4 bargaining position in their relation with the producers or marketers, proved by lots of misleading commercials exposing in many mass media. This paper aimed to describe the kinds of misleading commercials and then analyze it yuridically.Key words : penyalahgunaan iklan, perlindungan konsumen, Undang-undang Perlindungan Konsumen, penyelesaian konflik konsumen dan produsen.